Kinetic Release Studies of Antibiotic Patches for Local Transdermal Delivery - GÜNDÜZ, OĞUZHAN (MDPI, 2021)
This study investigates the usage of electrohydrodynamic (EHD)-3D printing for the fabrication of bacterial cellulose (BC)/polycaprolactone (PCL) patches loaded with different antibiotics (amoxicillin (AMX), ampicillin (AMP), and kanamycin (KAN)) for transdermal delivery. The composite patches demonstrated facilitated drug loading and encapsulation efficiency of drugs along with extended drug release profiles. Release curves were also subjected to model fitting, and it was found that drug release was optimally adapted to the Higuchi square root model for each drug. They performed a time-dependent and diffusion-controlled release from the patches and followed Fick's diffusion law by the Korsmeyer-Peppas energy law equation. Moreover, produced patches demonstrated excellent antimicrobial activity against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) strains, so they could be helpful in the treatment of chronic infectious lesions during wound closures. As different tests have confirmed, various types of antibiotics could be loaded and successfully released regardless of their types from produced BC/PCL patches. This study could breathe life into the production of antibiotic patches for local transdermal applications in wound dressing studies and improve the quality of life of patients.
Keywords: electrohydrodynamic printing; antibiotic patches; drug release; polymer; bacterial cellulose; DRUG-DELIVERY; BACTERIAL CELLULOSE; POLYCAPROLACTONE SCAFFOLDS; SUSTAINED-RELEASE; FIBERS; NANOPARTICLES; FABRICATION; STRATEGIES; SYSTEM; CELL